(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Echinococcosis of the heart is a severe zooanthroponotic disease, which is characterized by a long chronic course, severe organ and systemic pathology, leading to disability and often to the death of the patient. From the moment of infection to the establishment of a diagnosis, there is a latent period lasting from 5 to 20 years.